2011
DOI: 10.1167/iovs.10-7132
|View full text |Cite
|
Sign up to set email alerts
|

Different Impact of ALS on Laminin Isoforms in Human Extraocular Muscles versus Limb Muscles

Abstract: The present study showed distinct impact of ALS on EOMs compared with limb muscles. The EOMs maintained a normal laminin composition in their NMJs, which may be instrumental for the fact that they are not typically affected in ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…This study is important because changes in laminin chains could be one of the causes associated with the NMJ degeneration seen in ALS, which may subsequently affects the progression of the disease. This is supported by the study of Liu et al (2011) which demonstrated altered laminins expression in ALS donors suggesting the potential involvement of laminins in NMJ degeneration of ALS (see Section 1.3; Dying-backward hypothesis in amyotrophic lateral sclerosis).…”
Section: The Involvement Of Transactive Response Dna Binding Protein mentioning
confidence: 64%
See 4 more Smart Citations
“…This study is important because changes in laminin chains could be one of the causes associated with the NMJ degeneration seen in ALS, which may subsequently affects the progression of the disease. This is supported by the study of Liu et al (2011) which demonstrated altered laminins expression in ALS donors suggesting the potential involvement of laminins in NMJ degeneration of ALS (see Section 1.3; Dying-backward hypothesis in amyotrophic lateral sclerosis).…”
Section: The Involvement Of Transactive Response Dna Binding Protein mentioning
confidence: 64%
“…A recent study by Liu et al (2011) found absent expression of laminin-α4 at the NMJs of limb muscles in ALS patients. This novel finding highlighted the potential involvement of laminins in ALS disease states.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations